Digital Literacy Training: Its Impact on Teachers in Busoga Region, Eastern Uganda - Martin Okoed; Emmanuel Acidri Bileti (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This study evaluated the impact of digital literacy training on teachers in Busoga region, Eastern Uganda. Specifically, it assessed the impact of digital literacy training on teachers' skills and knowledge, evaluated facilitators' effectiveness in delivering the training program, and investigated teachers' proposals for promoting ICT integration in secondary schools. Method: A convergent parallel mixed methods design was used; data was collected from 300 teachers through online questionnaires and focus group discussions. Results: It was revealed that the digital literacy training very positively impacted the skills/knowledge of teachers in the Busoga Region. Furthermore, the result indicated high satisfaction with the facilitators' skills and responsiveness. Finally, teachers proposed the need for infrastructure enhancement, capacity building, resource provision, connectivity, and incorporation of ICT tools like smartphones, laptops, and projectors in teaching and learning. Novelty: This study contributes valuable empirical insights to the discourse on digital literacy training, stressing its role in fostering effective teaching practices. As technology continues to evolve, understanding its nuanced impact on teachers becomes increasingly crucial for shaping the future of education.